1989
DOI: 10.1086/285019
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila paulistorum Endosymbiont in an Alternative Species

Abstract: The Drosophila paulistorum species complex consists of six known apparently separate semispecies: Amazonian, Andean, Centroamerican, Interior, Orinocan, and Transitional. They are the intracellular cytoplasmic bearers of an L-form (cellwall-deficient) microorganism belonging to the genus Streptococcus. (For full histories of the D. paulistorum semispecies, see Ehrman and Powell 1982;Ehrman et al. 1987. For the bacteriology of the streptococcal L-form, see Somerson et al. 1984b.) Drosophila pavlovskiana, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In Drosophila paulistorum sterility of males is induced by the pro liferation of vertically transmitted Staphylococci. The adaptive significance of this phenomenon is uncertain as this sterilization is only found in hybrid males (Ehrman et al 1989;Ehrman & Kernaghan 1971). Similarly, in hybrid crosses between Heliothis species (Lepidoptera) male-specific sterility due to maternally inherited genes has been shown (Lansman et al 1983).…”
Section: Late Male Killingmentioning
confidence: 99%
“…In Drosophila paulistorum sterility of males is induced by the pro liferation of vertically transmitted Staphylococci. The adaptive significance of this phenomenon is uncertain as this sterilization is only found in hybrid males (Ehrman et al 1989;Ehrman & Kernaghan 1971). Similarly, in hybrid crosses between Heliothis species (Lepidoptera) male-specific sterility due to maternally inherited genes has been shown (Lansman et al 1983).…”
Section: Late Male Killingmentioning
confidence: 99%
“…Furthermore, male infertility in inter-semispecies crosses was not relieved in matings using stocks which had been "cured" of DpLE. Previous surveys of D. paulistorum tissues for the occurrence of bacteria using electron microscopy Kernaghan, 1971, 1972;Daniels and Ehrman, 1974;Ehrman et al, 1992) con-eluded that members of this species complex harbor a single, pleomorphic, mycoplasma-like microorganism. Drosophila paulistorum clearly harbors multiple bacterial species and the interpretation of these findings requires revision in this light as well as based upon recent advances in determinative microbiology using PCR generally (Ward et al, 1990;Amann et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Early work on D. paulistorum demonstrated that hybrid male sterility had an infectious basis since injection of testis extracts from one semispecies into females of another yielded complete sterility in all of the host's male progeny (Williamson et al, 1971;Ehrman and Kernaghan, 1972). Ultrastructural studies revealed numerous "mycoplasma-like" microorganisms, primarily in gonadal tissues and embryos (Ehrman and Kernaghan, 1971;Daniels and Ehrman, 1974;Ehrman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This system, along with the t system in mice, is autosomal and, yet, causes sterility in only one sex. Furthermore, there are even cytoplasmic systems of sex-specific hybrid infertility in Drosophila (Ehrman et al, 1989). Finally, mosquitoes, which provide support for the Rule, do not have dimorphic sex chromosomes; sex is determined by sex factors on chromosomes that engage in recombination (Bull, 1983).…”
Section: Heterogametic Sexmentioning
confidence: 99%